Optimizing Coal Transfer Productivity at Taboneo: A Socio-Technical Analysis of STS Operations - Mohamad Nufel; Lili Purnamasita; Meilina Nurhasanah Hutagaol (Yayasan Literasi Sains Indonesia, 2025)
This qualitative study investigates the determinants of coal loading-unloading productivity at the Ship-to-Ship (STS) Transfer Taboneo in Indonesia. Through thematic analysis of interviews, observations, and documents involving crane operators, port managers, and ship crews, the research reveals a